2014
DOI: 10.1037/abn0000003
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfocusing in schizophrenia: Evidence from interactions between working memory and eye movements.

Abstract: Recent research suggests that processing resources are focused more narrowly but more intensely in people with schizophrenia (PSZ) than in healthy control subjects (HCS), possibly reflecting local cortical circuit abnormalities. This hyperfocusing hypothesis leads to the counterintuitive prediction that, although PSZ cannot store as much information in working memory as HCS, the working memory representations that are present in PSZ may be more intense than those in HCS. To test this hypothesis, we used a task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 58 publications
3
40
1
Order By: Relevance
“…Similarly, physically salient “color singleton” distractors cause no more interference with visual search performance in PSZ than in HCS (Leonard, Robinson, Hahn, Gold, & Luck, 2014). In contrast, the present ERP results and two previous behavioral studies (Luck et al, 2014; Mayer et al, 2012) indicate that PSZ exhibit exaggerated distraction by items that partially match active target representations.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, physically salient “color singleton” distractors cause no more interference with visual search performance in PSZ than in HCS (Leonard, Robinson, Hahn, Gold, & Luck, 2014). In contrast, the present ERP results and two previous behavioral studies (Luck et al, 2014; Mayer et al, 2012) indicate that PSZ exhibit exaggerated distraction by items that partially match active target representations.…”
Section: Discussioncontrasting
confidence: 99%
“…This hyperfocusing hypothesis accounts for aberrant patterns of reaction time, accuracy, eye movements, and event-related potentials (ERPs), including experiments in which PSZ exhibit enhanced attentional benefits and enhanced working memory-related neural activity compared to HCS (e.g., Gray et al, 2014; Hahn et al, 2012; Leonard, Kaiser, et al, 2013; Luck et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…However, other recent studies have also suggested a tendency of PSZ to hyperfocus processing resources. [12][13][14] A way of shedding light onto the nature of the disproportionately large spatial cueing effect in PSZ is by studying brain activity differences relative to HCS that accompany this phenomenon. In a previous functional Magnetic Resonance Imaging (fMRI) study of the SARAT in healthy participants, 15 we have shown that brain regions typically recruited by top-down attentional resource allocation, [16][17][18] often termed the dorsal attention network, [19][20][21] display step-wise greater activation with fewer cued target locations, ie, with a progressively narrow attentional focus.…”
Section: Introductionmentioning
confidence: 99%